A robust Delaunay-AFT based parallel method for the generation of large-scale fully constrained meshes. (February 2020) - Yu, Fei; Zeng, Yan; Guan, Z.Q.; Lo, S.H.
Highlights: Domain decomposition method able to handle complex geometries. Parallel distributed mesh generation method based on the Delaunay-AFT method. FEM mesh of the complex model with more than ten billion elements were generated. FEM mesh with more than ten billion elements generated on workstation in parallel. Abstract: Making full use of a sequential Delaunay-AFT mesher, a parallel method for the generation of large-scale tetrahedral meshes on distributed-memory machines is developed. To generate meshes with the required and the preserved properties, a Delaunay-AFT based domain decomposition (DD) technique is employed. Starting from the Delaunay triangulation (DT) covering the problem domain, this technique creates a layer of elements dividing the domain into several zones. The initially coarsely meshed domain is partitioned into DTs of subdomains which can be meshed in parallel. When the size of a subdomain is smaller than a user-specified threshold, it will be meshed with the standard Delaunay-AFT mesher. A two-level DD strategy is designed to improve the parallel efficiency of this algorithm. A dynamic load balancing scheme is also implemented using the Message Passing Interface (MPI). Out-of-core meshing is introduced to accommodate excessive large meshes that cannot be handled by the available memory of the computer (RAM). Numerical tests are performed for various complex geometries with thousands of surface patches. Ultra-large-scale meshes with more than ten billion tetrahedral elements have been created. Moreover, the meshes generated with different numbers of DD operations are nearly identical in quality: showing the consistency and the stability of the automatic decomposition algorithm.